Influences of Psychological Factors and Rehabilitation Adherence on the Outcome Post Anterior Cruciate Ligament Injury/Surgical Reconstruction - Mendonza, M; Patel, H; Bassett, SF (New Zealand Society of Physiotherapists, 2007)
Objective: To systematically review research that has investigated the relationships between psychosocial factors, adherence and outcomes of rehabilitation following ACL injury/reconstruction. Methods: A systematic literature search of the EBSCO, CINAHL, PEDro, PsycINFO and SPORT Discus databases was conducted by two of the authors independently. A critiquing tool was developed to critically evaluate the studies on the basis of their purpose, design, participants, measures and results. Results: 117 articles were found, of which 10 met the criteria for inclusion in the review. The results of the studies point to the existence of the psychosocial-adherence and adherence-outcome relationships. Strengths of the research were the large sample sizes and the multifaceted measurement of the three variables of interest. However very few studies used longitudinal and cause-effect study designs to evaluate the variables. Conclusion: Psychological factors in particular motivation, self-efficacy and perceptions of personal control were positively associated with adherence behaviours and rehabilitation outcomes. There were contradictory findings for the adherence-rehabilitation outcome relationship, with it being positive for young adults, but negative for older adults, which is suggestive of a dose-response effect. Future research should focus not only on the relationships between psychosocial factors, functional outcomes and adherence, but should also investigate amount of adherence required to produce optimal rehabilitation outcomes.
Keywords: Adherence; Psychosocial factors; Functional outcomes; Physiotherapy rehabilitation; Anterior cruciate ligament injuries